STUDY OF IN VIVO PHARMACOKINETIC DRUG INTERACTIONS OF CURCUMIN ON TACRINE - Alavala, Rajasekhar Reddy; Katahala, Prathusha; Thipparapu, Ganapathi; Kulandaivelu, Umasankar; Boyapati, Shireesha; Mantripragada, Bhagavan Raju (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Tacrine is a potent acetylcholine esterase inhibitor (AChEI), and curcumin has been recently proven to possess AChEI, amyloid Î² aggregation inhibitory activity in addition to its diverse pharmacodynamic nature. Tacrine undergoes biological transformation by cytochrome P450 (CYP 1A2) to a hydroxy metabolite, which is hepatotoxic. Curcumin is known for its inhibitory nature for various metabolic enzymes along with CYP1A2. The present study was undertaken to evaluate the influence of curcumin on the disposition kinetics of tacrine and to assess its impact on dosage regimen. Methods: It was hypothesized that the simultaneous administration of curcumin and tacrine can minimize the toxicity along with increased absorption of tacrine and curcumin into the biological system during the treatment of Alzheimer's patients. Results and Discussion: Hence, an attempt was made to develop a simple, precise, accurate, and cost-effective reversed-phase high-performance liquid chromatography method for simultaneous determination of curcumin and tacrine and also to estimate the effect of curcumin on absorption of tacrine, in rat plasma. Conclusion: Concomitant administration of curcumin with tacrine improved the parameters such as Cmax and AUC, which indicates that the curcumin would improve the absorption of tacrine.